Susceptibility of Tigecycline against Carbapenem Resistant Enterobacteriaceae - Madeeha Fatima; Faisal lqbal Afridi; Hareem Gohar (ziauddin University, 2024)
Background: Enterobacteriaceae, a large family of Gram-negative bacteria, are one of the commonest etiological agents causing serious bacterial infections to humans. Carbapenems are the group of antibiotics with a broad spectrum of antimicrobial action. Infections caused due to Carbapenem resistant Enterobacteriaceae (CRE) are a huge challenge for existing medical practice. Therefore, this project aimed to find out the antimicrobial susceptibility pattern of Tigecycline against CRE.  Methods: This cross-sectional study with non-probability consecutive sampling was done at Ziauddin Hospital Microbiology Laboratory from 15th August 2017 to 15th April 2018. Accordingly, 151 isolates of CRE were collected from cultures of blood, respiratory tract, wound pus and other body fluids. The growth inhibition zones were measured following the Food and Drug Administration (FDA) disk diffusion breakpoint criteria. Frequencies and percentages were computed for gender, microorganism, and antimicrobial susceptibility. Chi-squared test was applied and p≤ 0.05 was considered as statistically significant.   Results: Klebsiella species were most commonly isolated pathogen, 67.5% (n=102) followed by Escherichia coli (E. coli) 23.2% (n=35), Enterobacter 7.3% (n=11) and Serratia species 2% (n=3). Tigecycline was 97% (34 /35) sensitive for E. coli, 86.3% (88/102) for Klebsiella species), 91% (10/11) for Enterobacter species, and 100% for Serratia species. Klebsiella species showed the highest rate of resistance to tigecycline i.e., 13.7% of the total Klebsiella isolates. Conclusion: Among the Enterobacteriaceae family, Klebsiella species have the greatest ability to acquire resistance. Tigecycline showed good activity against isolates of CRE recovered from infections of skin, soft tissue, intra-abdomen, lower respiratory tract and blood stream. Keywords: Carbapenems; beta-Lactamases; Anti-Bacterial Agents; Tigecycline; Klebsiella; Escherichia coli.